Intellectual capital reporting among large Malaysian companies and their determinants - Robiah, Abu Bakar (2018)
In this new economy, intellectual capital (IC) plays an important role compared to the physical assets in achieving a company’s value and success. This study examines the IC disclosure practices in the 2006 annual reports of the 70 largest Malaysian companies listed on Bursa Malaysia. IC disclosures were captured using content analysis, and an ‘Operational Definition of IC’ was used to measure the extent of IC reporting. The results indicated that the sampled companies provided a generous quantity of IC information. However, the inconsistency in the application of content analysis, as well as an absence of specific guidelines on IC, had led to substantive difference in IC reporting practices. This study also examines the possible determinants of IC disclosure practices from three perspectives: IC value in a company, corporate governance structure and company characteristics. The results of the regression analyses based on the four measures of IC disclosure, i.e. total IC, total human capital, total structural capital, and total relational capital, indicated significant associations with certain variables under these three perspectives. These findings offer support for the proposition that Malaysian companies disclose their IC information to legitimise their activities and performance, since management considers these information as part of their value creation process and is considered as value relevant information to their stakeholders. This research also provides evidence that there is a need to have a guideline (IC disclosure index), which can be used as a basis for IC reporting framework. A set of guidelines for companies in measuring and reporting of IC would be advantageous to both preparers and users of financial information. Such practices would enhance the consistency of IC disclosure.